Use propositional logic to prove that the statement is valid:
1) [A → (B → C)] ^ (A V ~D) ^ B → (D → C)
2) (A → B) ^ [B → (C → D)] ^ [A → (B → C)] → (A → D)
3) A V B, A → C, B → C → C
Hope to get some help by getting some sort of step-to-step instructions.
First, you need a lot more brackets/parentheses.
How much propositional logic do you know? In particular, if you know the soundness and completeness theorem of first order propositional calculus then you can do with a truth table. If not, are you allowed to use derived argument form or just modus ponen?